2012
DOI: 10.1167/iovs.11-8461
|View full text |Cite
|
Sign up to set email alerts
|

The Photopic Negative Response of the Flash Electroretinogram in Multiple Sclerosis

Abstract: Photopic ERG PhNR amplitudes in MS patients are significantly reduced in eyes with and without a history of ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 43 publications
8
57
0
2
Order By: Relevance
“…It is well known that within the first 3 to 6 months following acute optic neuritis (ON), significant axonal and neuronal loss occurs (Costello et al, 2008, Syc et al, 2012), resulting in permanent visual dysfunction. MS eyes, even without a history of optic neuritis (non-ON eyes) can have significant abnormalities in structure (Green et al, 2010, Narayanan et al, 2014) and in visual function (Brusa et al, 1999, Laron et al, 2009, Wang et al, 2012). Furthermore significant changes in both structural and functional measures occur over time in ‘clinically-silent’ MS eyes with or without a history of ON (Narayanan et al, 2014, Narayanan et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that within the first 3 to 6 months following acute optic neuritis (ON), significant axonal and neuronal loss occurs (Costello et al, 2008, Syc et al, 2012), resulting in permanent visual dysfunction. MS eyes, even without a history of optic neuritis (non-ON eyes) can have significant abnormalities in structure (Green et al, 2010, Narayanan et al, 2014) and in visual function (Brusa et al, 1999, Laron et al, 2009, Wang et al, 2012). Furthermore significant changes in both structural and functional measures occur over time in ‘clinically-silent’ MS eyes with or without a history of ON (Narayanan et al, 2014, Narayanan et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, the PhNR has been shown to originate from the spiking activity of retinal ganglion cells (RGCs) and their axons with additional contribution from amacrine cells and glia. [1][2][3][4][5] Studies in humans have reported the PhNR amplitude to be significantly reduced in glaucoma, [6][7][8] optic nerve atrophy, 9,10 and ischemic retinal diseases. [11][12][13] Further, the decrease in PhNR in these conditions may precede detectable changes in morphology and visual function, enabling the possibility of early object assessment of retinal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Accumulating evidence from clinical cases has demonstrated the PhNR can be used to evaluate RGC function in patients with retinal and optic nerve diseases affecting the RGCs. [6][7][8][9][10][11][12][13][14][15][16] In glaucoma patients, clinical studies have shown that the amplitude of the PhNR was correlated with the visual sensitivity, retinal nerve fiber layer (RNFL) thickness and optic disc topography. 12 However, the results also show that the diagnostic sensitivity of the full-field PhNR was not high for eyes with early-stage glaucoma.…”
Section: Introductionmentioning
confidence: 99%